Crossbow injuries to the thumb - Vogels, E.; Mahajan, A.; Klena, J. (The Journal of Sports Medicine and Physical Fitness, 2015)
Archery injuries resulting in significant digital impairment are uncommon. The purpose of this study was to review seven patients treated at our institution for injuries of the left thumb sustained during recreational use of a crossbow. We reviewed all thumb injuries caused by crossbow use treated at Geisinger Health System between August 2011 and November 2012. The electronic medical records were reviewed to document mechanism of injury, injury pattern, patient characteristics, treatment, and outcomes. Seven patients were identified with injury to their left thumb, six males and one female. Two patients sustained contusions; two nerve injuries; one dorsal skin loss; one nail complex injury; two extensor tendon injury; three distal phalangeal fracture; one interphalangeal fracture-dislocation; two complete or partial amputations. These injuries were treated with standard techniques. Injuries sustained during recreational crossbow use result from trauma to the left thumb which is placed in a forward position on the crossbow stock. Increasing popularity of crossbow usage has made these injuries more prevalent. Standard techniques of treating hand trauma are sufficient to manage these injuries. With proper education and safety mechanisms, these injuries are preventable.